Challenges and Cybersecurity Threats in Digital Economic Transformation - Desta Lesmana; Mochammmad Afifuddin; Agus Adriyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The integration of digital technology in economic transformation can introduce new risks and threats caused by the emergence of new technologies and features in the digital economy. It is crucial for governments, as implementers and overseers of the economy, to identify potential risks and threats in order to ensure the security of the national economy during the digital economic transformation. The efficiency of the measures developed and implemented to minimize risks and eliminate threats to national economic security depends on the quality and precision of the policies implemented. A comprehensive approach to analyzing the risks and threats posed by cyber threats in the digital economy is necessary and should cover all economic processes, particularly the relationships among the actors involved in the economic process.